Implications of Coexisting Aortic Regurgitation in Patients With Aortic Stenosis - Ngiam, Jinghao Nicholas; Chew, Nicholas W.S.; Pramotedham, Thanawin; Tan, Benjamin Yong-Qiang; Sia, Ching-Hui; Loh, Poay Huan; Ruan, Wen; Tay, Edgar; Kong, William K.F.; Yeo, Tiong-Cheng; Poh, Kian-Keong (JACC. Asia, 2021)
Aortic regurgitation (AR) is a common comorbidity in patients with aortic stenosis (AS), but coexisting AR has often been excluded from major clinical studies on AS. The impact of coexisting AR on the natural history of AS has not been well-described. The authors compared clinical outcomes in medically managed patients with moderate-to-severe AS with or without coexisting AR. Consecutive patients (N = 1,188) with index echocardiographic diagnosis of moderate-to-severe AS (aortic valve area <1.5 cm2) were studied. All patients were medically managed and were divided into those with coexisting AR (at least moderate severity) and those without. Adverse composite clinical outcomes were defined as mortality or admissions for congestive cardiac failure on subsequent follow-up. The authors compared differences in clinical profile and outcomes between the groups. There were 88 patients (7.4%) with coexisting AR and AS. These patients did not differ significantly in age, but had lower body mass index (22.9 ± 3.8 vs 25.3 ± 5.1 kg/m2), lower diastolic blood pressure (68.7 ± 10.7 vs 72.2 ± 12.3 mm Hg), larger end-diastolic volume index (68.8 ± 18.8 vs 60.4 ± 17.8 mL/m2) and larger left ventricular mass index (118.6 ± 36.4 vs 108.9 ± 33.1 g/m2). The prevalence of cardiovascular risk factors did not differ significantly. Coexisting AR was associated with increased incidence of adverse outcomes (log-rank 4.20; P = 0.040). On multivariable Cox regression, coexisting AR remained independently associated with adverse outcomes (HR: 1.36; 95% CI: 1.02-1.82) after adjusting for age, AS severity, left ventricular ejection fraction, and year of study. In patients with AS, coexisting AR was associated with changes in echocardiographic profile and adverse outcomes. [Display omitted]